Feeling the heat: Climate risks and the cost of sovereign borrowing - John Beirne; Nuobu Renzhi; Ulrich Volz (Asian Development Bank Institute (ADBI), 2020)
This paper empirically examines the link between the cost of sovereign borrowing and climate risk for 40 advanced and emerging economies. Controlling for a large set of domestic and global factors, the paper shows that both vulnerability and resilience to climate risk are important factors driving the cost of sovereign borrowing at the global level. Overall, we find that vulnerability to the direct effects of climate change matter substantially more than climate risk resilience in terms of the implications for sovereign borrowing costs. Moreover, the magnitude of the effect on bond yields is progressively higher for countries deemed highly vulnerable to climate change. Impulse response analysis from a set of panel structural VAR models indicates that the reaction of bond yields to shocks imposed on climate vulnerability and resilience become permanent after around 12 quarters, with high risk economies experiencing larger permanent effects on yields than other country groups.
Keywords: F32; F41; F62; 330; climate risk; cost of sovereign borrowing